Diverse Routes in the Development of Obesity - Preeti; Sharma, Rahul Kumar; Shivani Chopra; Chopra, Hitesh (Scripta Medica, 2025)
Obesity, a prevalent community health concern, is a diseased state characterised by an abundance of adipose tissue. This condition arises from notable transformations resulting from modern civilisation, where overconsumption and sedentary behaviours have become commonplace in contemporary society. Obesity’s prevalence and associated health effects present a significant public health challenge affecting both physical and cognitive health and executive function impairments are commonly observed. In obese individuals, suggesting a complex interplay between weight and cognitive well-being, the gut microbiota serves as a bridge between external factors like diet and lifestyle and the body’s physiological processes, potentially illuminating the intricate pathways connecting these health issues. Unhealthy dietary patterns characteristic of Western diets contributes to imbalances in the gut microbiota, which can exacerbate obesity-related complications. Research indicates that the gut microbiota linked to obesity may instigate various changes in the body, including disruptions in the hypothalamic-pituitary-adrenal axis. These disruptions can lead to disturbances in hormone regulation, desensitisation of leptin receptors, resistance and neuroinflammation. It is crucial to grasp the interplay between altered the hypothalamic-pituitary-adrenal (HPA) axis activity and long-term consequences of obesity, considering factors like age, gender and racial disparities. Examining the intricate connection between neuro-immunology and immune metabolism, particularly in adipose tissue where immune cells and the sympathetic nervous system (SNS) play crucial roles, can provide insights into the complex mechanisms of obesity-related health issues. This review emphasises the multifaceted mechanisms in the development of obesity, laying the groundwork for understanding various avenues that could be explored for innovative and effective pharmaceutical interventions in obesity management.
Keywords: Obesity; Neuroinflammatory diseases; Gastrointestinal microbiome; Hypothalamo-hypophyseal system; Adrenal glands; Immunology; Leptin; Resistance